Biomechanical Comparison of Two Locking Plate Constructs for the Stabilization of Feline Tibial Fractures - Hottmann, Natasha M.; Johnson, Matthew D.; Banks, Scott A.; Tuyn, David; Lewis, Daniel D. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objectives The aim of this study was to compare the biomechanical characteristics of locking compression plate (LCP) and conical coupling plate (CCP) constructs for the stabilization of experimentally induced gap fractures in cat tibiae.Materials and Methods Pelvic limbs were harvested from eight cat cadavers. Paired tibiae were stripped of all soft tissues, and randomly assigned to the LCP or CCP stabilization group. An eight-hole 2.7 mm LCP or a six-hole 2.5 mm CCP was applied to the medial surface of each tibia. A 1-cm segment of the tibia was excised centrally beneath the plate. The specimens were potted, then tested in non-destructive four-point craniocaudal and mediolateral bending, followed by non-destructive axial compression. Each construct was subsequently loaded to failure in axial compression. Bending and axial stiffness, yield load and failure load were calculated for each specimen.Results The LCP constructs were significantly stiffer than the CCP constructs when subjected to non-destructive bending and axial loading. Craniocaudal bending stiffness was significantly greater than mediolateral bending stiffness for both constructs. Yield load and failure load were significantly greater for LCP constructs compared with CCP constructs.Clinical Significance LCP may be a more suitable implant for stabilizing complex diaphyseal tibial fractures in cats. Additional supplemental fixation should be considered when using CCP to stabilize unreconstructed diaphyseal tibial fractures in cats. Further clinical investigation of both implants is recommended.
Keywords: locking plates; tibial fracture; cats; biomechanical testing; conical coupling plate